2020
DOI: 10.3390/biom10081095
|View full text |Cite
|
Sign up to set email alerts
|

Glutenin and Gliadin, a Piece in the Puzzle of their Structural Properties in the Cell Described through Monte Carlo Simulations

Abstract: Gluten protein crosslinking is a predetermined process where specific intra- and intermolecular disulfide bonds differ depending on the protein and cysteine motif. In this article, all-atom Monte Carlo simulations were used to understand the formation of disulfide bonds in gliadins and low molecular weight glutenin subunits (LMW-GS). The two intrinsically disordered proteins appeared to contain mostly turns and loops and showed “self-avoiding walk” behavior in water. Cysteine residues involved in intramolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 93 publications
(177 reference statements)
3
22
0
Order By: Relevance
“…The low charge content of γ gliadin and its truncated domains suggests that they belong to the weak polyelectrolytes/polyampholytes category which could adopt globules or tadpoles conformations (compact con formation) [37]. Similar results were recently obtained for α gliadin and low molecular weight glutenin [35]. Besides, the composition anal ysis of γ gliadin amino acid sequence suggests a significant enrichment in proline and glutamine as compared to other IDPs (see Supplementary Fig.…”
Section: Synthesis and Purification Of Peptidessupporting
confidence: 77%
“…The low charge content of γ gliadin and its truncated domains suggests that they belong to the weak polyelectrolytes/polyampholytes category which could adopt globules or tadpoles conformations (compact con formation) [37]. Similar results were recently obtained for α gliadin and low molecular weight glutenin [35]. Besides, the composition anal ysis of γ gliadin amino acid sequence suggests a significant enrichment in proline and glutamine as compared to other IDPs (see Supplementary Fig.…”
Section: Synthesis and Purification Of Peptidessupporting
confidence: 77%
“…Gliadin showed monomeric units nonetheless hordein shows the existence of some higher ordered aggregates. This fact is also supported by amino acid composition that the higher proportion of basic AA and S-containing AA residues in hordein shows its tendency in formation of aggregates through strong electrostatic and hydrostatic interaction 9 . The secalin showed a bimodal PSD with two populations in the solution.…”
Section: Resultsmentioning
confidence: 68%
“…The inter-planar spacing, 'd', was calculated from the peak positions using Bragg's equation ( 9 reported that α-gliadin and LMW-GS showed a similar secondary structure propensity in the absence of intra-molecular disulphide bonds with a relatively uniform distribution of α-helix and/or β-sheet whereas when intra-molecular disul de bonds are involved there is an increased tendency for β-sheet/strand for the amino acid involved in these speci c bonds. It can be inferred from the previous study that the prolamins under investigation also had α-helix and/or β-strand structures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations